Evaluation UX Design on GGWP Tourney Application Using HCD and Heuristic Evaluation Methods - Heri Setyo Nugroho; Anisa Herdiani; Rosa Reska Riskiana (Journal of Computer System and Informatics (JoSYC), 2022)
The rapid developments in technology make the information spread faster, especially in the electronic sports industry (eSports). Game tournament information is essential to gamers since they strive to obtain accurate and easy-to-understand information about esports. The GGWP Tourney application is a mobile application that provides information and means to purchase e-sports competitions online. However, the GGWP Tourney application is still in the development stage so there are still many user experience problems, especially in the usability and journey of the application. Therefore, analysis and evaluation of the usability of the GGWP Tourney application are carried out so that it is in accordance with what users expect. In this study, usability evaluation was carried out using Heuristic Evaluation as a method of evaluating usability values and designing solutions using the Human Centered Design (HCD) method according to user perceptions based on the results of the evaluation carried out. The evaluation has been carried out in two stages, namely the initial stage and the stage after designing the solution design. The results of the initial evaluation found 12 problems and the severity rating value had an average greater than 2 so improvements were made to the application user interface. While the second evaluation stage in the solution design shows the number of problems found only 3 and the severity rating value is less than 2 so that no further repairs are carried out. Based on these results, the heuristic evaluation method can reduce the number of problems in the GGWP Tourney application from 13 problems to 3 remaining problems. This methods be used to determine the usability value of an application that can be used to improve the user experience of the application.